Improvements on Cardiovascular Diseases Risk Factors in Obese Adolescents: A Randomized Exercise Intervention Study - Gomes Silva, Humberto Jose; Andersen, Lars Bo; Lofrano-Prado, Mara Cristina; Barros, Mauro V. G.; Freitas, Ismael Fortes [UNESP]; Hill, James; Prado, Wagner Luiz do (Human Kinetics Publ Inc, 2015)
Background: It is unclear how different exercise intensities affect cardiovascular disease (CVD) risk factors in obese adolescents. The aim of this study was to compare the effects of high-intensity (HIT) vs. low-intensity (LIT) aerobic training on CVD risk factors in obese adolescents. Methods: Forty-three obese adolescents (age: 15.7 +/- 1.3 years, BMI: 34.3 +/- 4.1kg/m(2)) participated this study either HIT (corresponding to ventilatory threshold I; N = 20) or LIT (20% below ventilatory threshold I; N = 23) for 12 weeks. All sessions were isocaloric (350 kcal). All participants received the same nutritional, psychological, and clinical counseling. Subjects were assessed in fatness, fitness, lipid profile, and glucose at baseline and after 12 weeks. The CVD risk factors assessed were waist circumference (WC), total cholesterol (TC), high-density lipoprotein (HDL), glucose, and fitness, which were single and clustered analyzed (z scores sum). Results: Body mass, Body Mass Index, fatness, and WC were improved (P < .001) in both groups. The sum of z scores (WC + TC + glucose-fitness-HDL) improved in both HIT (12 weeks = -2.16 SD; Cohen's d = .45) and LIT (12 weeks = 2.13 SD; Cohen's d = .60) without groups differences. Changes in fitness were associated with changes in WC (r = .48; P = .003). Conclusion: HIT does not promote any additional improvements in CVD risk factors than LIT in obese adolescents.
Keywords: physical activity; health; obesity; multidisciplinary therapy